Les risques environnementaux en 2020 : une feuille de route pour INRAE - Eckert, Nicolas; Rigolot, Éric; Caquet, Thierry; Naaim, Mohamed; Allard, Denis; Erdlenbruch, Katrin; Garric, Jeanne; Gohin, Alexandre; Giacona, Florie; Lang, Michel; Marette, Stephan; Membré, Jeanne-Marie; et al. (Natures sciences sociétés (Montrouge), 2023)
INRAE a mené une réflexion prospective collective sur les risques environnementaux dans une perspective inter- et transdisciplinaire inscrite dans le cadre des sciences de la durabilité. Les risques pour les sociétés, les écosystèmes et les milieux ont été considérés conjointement et de façon holistique. Cet article résume les quatre priorités scientifiques identifiées, exprimées de manière transverse. Une feuille de route pour atteindre ces objectifs est également proposée, incluant les ressources humaines, les infrastructures, l’animation scientifique et les partenariats. Ces conclusions devraient participer à la structuration de la recherche française et internationale, et constituer ainsi une contribution significative à l’effort requis par l’urgence environnementale actuelle. INRAE conducted a collective prospective analysis on environmental risks in an inter- and transdisciplinary perspective within the framework of sustainability sciences. Risks for societies, ecosystems and the environment have been considered jointly and in a holistic way. This article sums-up the four scientific priorities identified, expressed in transverse ways: (i) the risk concept as a research object within a nonstationary context, (ii) from hazard/danger to decision within a systemic framework, (iii) emerging risks of high societal resonance, (iv) multiple risks. A roadmap to reach these goals is also proposed, including human resources, infrastructures, scientific animation and partnerships. These conclusions should participate to the structuration of French and international research communities, and thus constitute a significant contribution to the effort required by the current environmental emergency.